INCIDÊNCIAS DE LESÕES DO FUTEBOL DE AMPUTADOS INCIDENTS OF AMPUTEE FOOTBALL INJURIES - Alberto Santos, Carlos; Barbosa de Souza, Karina; Moussa, Laila; R Pinez, Marcia (LINKSCIENCEPLACE, 2026)
The amputation is the removal chirurgical total or partial of the member of the body. Even the football being a very popular sport in Brazil yet the amputee football is not common. The high incidence of lesion among amputee football players happens mostly because they do not have a good muscle preparation.The goals: Verify the most common lesion and its frequency on amputee football players.Methodology: The methodology used was descriptive and quantitative made by a questionnaire in November of 2016 in order to verify the most common lesion on this sport. The 32 football players who had participated were from the “Smel Mogi Só Vida amputee football team”.Results: The average age of the athletes on this research was 32.8 years old and they do training 3.5 hours a week. 50 % of them said they have had a lesion.The research shows that the most common type of lesion was a transfemoral which happened on 13 athletes and most of the time the knee was the articulation lesioned in 30% of them. The main lesion related by the athletes was the sprain with 41.38% and 44.44% said that the lesion happened when they were trying to block the opponent.Final considerations: The conclusion is that the sprain is the lesion which happens most of the time on amputee football players and to avoid this is necessary to prioritize the prevencion.